Marine control practice - Taylor, D. A., M. Sc (Marine engineering series., 1987)
Marine Engineering Series: Marine Control Practice deals with the instrumentation and its associated control systems that are found onboard ships. The book covers topics such as the measuring instruments and control signals for different parameters; system analysis; process and kinetic control systems; and commercially available equipment. Also covered in the book are correcting units such as actuators and valves; the control systems for boilers, turbines, auxiliary equipment; and control involving computers. The text is recommended for those who need to complete the Certificates of Competency.